The Development of Emotional Intelligence Scale in Sport Coaching - Seunghyun Hwang; Boram Kim; Hoseok Kang (Korea Institute of Sport Science, 2021)
Purpose The purpose of this study was to develop the Emotional Intelligence Scale in Sport Coaching(EISSC) based on the emotional intelligence trait model. Methods The participants were 236 professional sports coaches by the purposive sampling methods via e-mails. 48 preliminary items were developed by literature review among expert panels. Then, a total of 40 items were selected after the item-analysis. Exploratory factor analysis was conducted for construct validity and criterion validity was evaluated by Person's correlation with coaching efficacy scale and general emotional intelligence scale. An internal consistency, Cronbach's alpha coefficient, was used to see the reliability. Results The results of exploratory factor analysis presented a six sub-structure factors (Self-awareness, Awareness of others, Optimism, Utilization of emotion, Emotion regulation, Social skills) with 20 items, which explained 68.49% of the total variance. Criterion-related validity was supported by correlations with in coaching efficacy(r=.713) and general emotional intelligence(r=.647). Reliabilities were secured with Cronbach's alpha coefficient .854 for the total 20 items. Conclusions The EISSC can be used to provide an valid measure of emotional ability of coaches in sport.